A Comparative Study of the Effects of Nontoxic Chloride Treatments on CdTe Solar Cell Microstructure and Stoichiometry. Issue 21 (27th July 2015) - Williams, Benjamin L.; Major, Jonathan D.; Bowen, Leon; Keuning, Wytze; Creatore, Mariadriana; Durose, Ken
Abstract : This work presents the first systematic comparison of the effects of a range of chlorides (CdCl2, MgCl2, NaCl, and NH4 Cl) on the microstructure and chemical composition of CdTe/CdS/ZnO/SnO2 solar cells, providing valuable insight to the ubiquitous Cl‐activation process. Using X‐ray diffraction, it is shown that CdCl2 induces the greatest extent of recrystallization (standard deviation of texture coefficients, σ, reduces from 0.93 for as‐grown CdTe to 0.43) and minimizing stress (from 178 MPa for as‐grown material to zero). MgCl2 treatment also yields significant randomization of the CdTe texture ( σ = 0.55) but NaCl treatment does not ( σ = 1.10). A strong correlation between the extent of metallurgical changes induced by the chloride treatment (and consequently, device efficiency) and the dissociation energy of the cationCl bond is shown, thereby accounting for the ineffectiveness of NaCl (bond energy = 4.3 eV). From this, a mechanism for Cl activation is postulated. By X‐ray photoelectron spectroscopy it is also shown that the Te/Cd ratio at the back surface, and the Cl content at the CdTe–CdS interface, are both higher following CdCl2 ‐ and MgCl2 treatments (Te/Cd = 1.3–1.4, and 1–2 at% Cl) than following NaCl treatment (Te/Cd = 1.1, and 0 at% Cl). Abstract : The effectiveness of various chlorides for activating CdTe solar cells is explored, in view of replacing the highly toxic CdCl2 . It is shown that the chosen chloride must have a low dissociation energy (<4 eV) in order to catalyze the necessary metallurgical and stoichiometric changes. Significant insight into the Cl‐activation mechanism is gained from the results.